The Role of Social Media in Shaping Regulatory Policies for Digital Businesses: Business and Policy Perspectives - Mohammadi, Razieh; Sadeghi Jafari, Javad (Future of Work and Digital Management Journal, 2025)
This study aimed to analyze how social media influences the regulatory policy-making process in digital business ecosystems through agenda-setting, social mobilization, and direct policy impact. A mixed-methods design combining quantitative and qualitative approaches was adopted to capture both the measurable impact of social media and the deeper mechanisms behind it. The quantitative phase employed a stratified random sample of 384 social media users categorized as ordinary users, influencers, and digital experts. Data were collected through a 20-item online Likert-scale questionnaire, with reliability confirmed by Cronbach’s alpha (0.87) and content validity ensured by expert review. The qualitative phase included 15 semi-structured interviews with policy-makers, startup executives, and media specialists, complemented by content analysis of 5,000 tweets and 2,000 Instagram posts related to ride-hailing services and cryptocurrencies between 2018 and 2023. Quantitative data were analyzed using t-tests, ANOVA, and multiple regression in SPSS, while qualitative data underwent thematic analysis. Statistical analysis confirmed that social media significantly enhances public awareness (M = 4.32, p < .001) and drives social mobilization (M = 4.05, p < .001). Multiple regression revealed that awareness (β = .41, p < .001), social mobilization (β = .35, p < .001), and direct user–policy-maker interaction (β = .22, p < .01) each had a positive and significant impact on regulatory outcomes, collectively explaining 62% of the variance in policy change (R² = .62). ANOVA indicated significant differences among user categories, with influencers and experts exerting greater policy-shaping influence than ordinary users. Qualitative insights underscored three major themes: transparency enhancement, coordinated social pressure, and challenges from misinformation leading to reactive regulation. Social media has evolved from a communication platform into an institutional actor capable of shaping regulatory policies in digital business sectors. Recognizing and systematizing this influence can improve transparency, responsiveness, and legitimacy in policy-making, while also requiring safeguards to prevent reactionary and poorly informed decisions.